Gender and Regional Differences in the Life Expectancy in Russia - L. A. Rodionova; E. D. Kopnova; Л. А. Родионова; Е. Д. Копнова (Voprosy statistiki, 2020)
The relevance of the chosen topic is closely related to the development of a system for monitoring the implementation of the May Presidential Decree (2018) to increase life expectancy and improve the quality of life of the population. It has been stated that despite the positive dynamics of life expectancy over the past decade, Russia still has a huge regional differentiation (16,6 years for women, 18,2 years for men in 2016) and an average gender gap - 10,6 years. The choice of factors affecting the gender gap in life expectancy in Russian regions is supported by a conclusion most common in foreign studies that climatic conditions, living conditions, the quality of food and drinking water, alcohol consumption are essential components of public health and life expectancy.The article provides an overview of studies on assessment factors of life expectancy, presents the authors’ approach to identifying gender gaps in life expectancy, living conditions, and lifestyle affecting the indicator of life expectancy. The paper presents the results of a comparative analysis of gender gap in life expectancy in Russia and foreign countries. The paper studies the correlation between living conditions and lifestyle, and life expectancy.Classiﬁcation of the regions by the life expectancy at birth for men and women is an important component of this study. The authors used Rosstat data for 2016 and the k-means method to select three clusters of Russian regions taking into account gender, living conditions and lifestyle. The paper identiﬁes similar health problems of the regions that are associated with alcohol consumption, poor nutrition and poor quality of drinking water, poor housing and living conditions. The lowest life expectancy rates for men and women are recorded in regions of the 1st cluster (Jewish Autonomous Region, Republic of Tuva, Chukotka Autonomous Area). High mortality rates are a result of external causes. There is a poor quality of drinking water and poor nutrition, excessive alcohol consumption, and inadequate ...